2006
DOI: 10.1124/jpet.106.106054
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Delivery of the p38 Mitogen-Activated Protein Kinase Inhibitor SB202190 [4-(4-Fluorophenyl)-2-(4-hydroxyphenyl)-5-(4-pyridyl)1H-imidazole] in Renal Tubular Cells: A Novel Strategy to Treat Renal Fibrosis

Abstract: During renal injury, activation of p38 mitogen-activated protein kinase (MAPK) in proximal tubular cells plays an important role in the inflammatory events that eventually lead to renal fibrosis. We hypothesized that local inhibition of p38 within these cells may be an interesting approach for the treatment of renal fibrosis. To effectuate this, we developed a renal-specific conjugate of the p38 inhibitor SB202190 [4-(4-fluorophenyl)-2-(4-hydroxyphenyl)-5-(4-pyridyl)1H-imidazole] and the carrier lysozyme. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 32 publications
7
47
0
Order By: Relevance
“…The absence of cytotoxic effects observed for 17864-ULS-lysozyme is in agreement with previous studies performed with another renal-specific conjugate, ie, SB202190-ULS-lysozyme, directed against a different profibrotic kinase. 25 As anticipated, methionine-modified lysozyme alone was also non-toxic to HK-2 cells (data not shown). Figure 5 shows the plasma disappearance curves of 17864-ULS-lysozyme and sunitinib after a single intravenous injection of the compounds in mice.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 71%
See 2 more Smart Citations
“…The absence of cytotoxic effects observed for 17864-ULS-lysozyme is in agreement with previous studies performed with another renal-specific conjugate, ie, SB202190-ULS-lysozyme, directed against a different profibrotic kinase. 25 As anticipated, methionine-modified lysozyme alone was also non-toxic to HK-2 cells (data not shown). Figure 5 shows the plasma disappearance curves of 17864-ULS-lysozyme and sunitinib after a single intravenous injection of the compounds in mice.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 71%
“…11,[19][20][21][22] To avoid these side effects, targeted delivery of sunitinib to the target cells, ie, the proximal tubular cells of the kidneys, is a comprehensive approach. We have shown that small-molecule inhibitors can be delivered to the kidney by conjugation to lysozyme, [23][24][25] a low molecular weight protein that is rapidly filtered through the glomeruli of the kidneys and subsequently taken up at the apical membrane of proximal tubular cells via megalin receptor-mediated internalization. 26 Since sunitinib does not contain functional groups such as hydroxyl or primary amino groups that can be used for the coupling to lysozyme, we designed a sunitinib derivative that can be linked to lysozyme via the platinum (II)-based Universal Linkage System TM (ULS) (Kreatech Diagnostics, Amsterdam, The Netherlands).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the colon of these mice showed normal architecture at the histological analysis. 38 Furthermore, a novel strategy for local delivery of SB has been developed to treat renal fibrosis, 39 indicating that pharmacological manipulation of p38 is emerging as a potential therapeutic tool for a number of human diseases. In this sense, our study might have an even broader interest.…”
Section: Discussionmentioning
confidence: 99%
“…Although the long-term effects of p38 inhibition on the development of diabetic nephropathy have not been elucidated, study have shown that this intervention may attenuate the development of renal glomerular and interstitial lesions in non-diabetic models of kidney disease. 38,39 In an experimental model of diabetic cardiomyopathy, chronic p38 inhibition attenuated the left ventricular dysfunction and prevented cardiac inflammation. 40 In summary, renal cortical p38 MAPK activity and expression was increased in diabetic rats at early stages of nephropathy as well as in animals with advanced disease, as compared with age-matched non-diabetic animals.…”
Section: Renal P38 In Experimental Diabetesmentioning
confidence: 99%